Energy and Agricultural Development in the Red River Delta Provinces, Vietnam - Thuy, Duyen Dang Thi (International Journal of Energy Economics and Policy, 2023)
Agriculture is a traditional industry in Vietnam in general and the Red River Delta in particular. Agriculture has created many jobs and incomes for laborers in the locality and neighboring provinces over the past time. However, the production and consumption of energy such as gasoline, gas, petroleum and fuel in the Red River Delta are concerned and focused by local authorities and people. In particular, they emphasize green agriculture. This study investigates the long-term cointegration relationship between energy production and consumption on agricultural development and local economic growth. The author used long-term data of eleven provinces for calculation. The experimental results demonstrate that the independent variables explain 53.5% of the variation of the dependent variable and the rest (46.5%) can be explained by other causes. The research results show that 4 factors are agricultural labor (La), agricultural revenue (output) (REV), agricultural investment capital (Ia) and production and consumption of petroleum and gas (PE) has a positive impact on agricultural production value. The factor of energy production and consumption (EG) has a negative impact on the value of agricultural production in the Red River Delta. From there, the study proposes ways to use more efficiently the existing energy sources in the Red River Delta.